2016
DOI: 10.1002/ejoc.201501261
|View full text |Cite
|
Sign up to set email alerts
|

Biphenyl Bis(amino alcohol) Oxalamide Gelators: Complex Gelation Involving Coupled Equilibria, Central‐to‐Axial Chirality Transfer, Dia­stereoisomer Interconversion, and Self‐Sorting

Abstract: Chiral gelators 3 and 4, with two valinol‐ or leucinol‐oxalamido arms attached to the 2,2′‐positions of the proatropisomeric biphenyl group, were prepared, and their gels were studied. Compound (R,R)‐3 in the solution and gel states forms a mixture of major [(R,aR,R)‐3] and minor [(R,aS,R)‐3] diastereomers due to central‐to‐axial chirality transfer. 1H NMR studies of its toluene gel provide evidence of diastereomer interconversion and self‐sorting, which results in exclusive incorporation of (R,aR,R)‐3 into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Oxalamide compounds are of considerable interest due to their potential in biomedical applications [34][35][36][37][38][39][40][41][42][43][44][45], catalysis [46][47][48], foods [49], and self-assembling behavior to form gels [50][51][52][53][54][55][56]. The oxalamide functional group consists of two amide groups next to each other in reverse mode, connected by two consecutive carbonyl groups, which has been extensively used as supramolecular synthon to generate LMWGs [50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxalamide compounds are of considerable interest due to their potential in biomedical applications [34][35][36][37][38][39][40][41][42][43][44][45], catalysis [46][47][48], foods [49], and self-assembling behavior to form gels [50][51][52][53][54][55][56]. The oxalamide functional group consists of two amide groups next to each other in reverse mode, connected by two consecutive carbonyl groups, which has been extensively used as supramolecular synthon to generate LMWGs [50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Oxalamide compounds are of considerable interest due to their potential in biomedical applications [34][35][36][37][38][39][40][41][42][43][44][45], catalysis [46][47][48], foods [49], and self-assembling behavior to form gels [50][51][52][53][54][55][56]. The oxalamide functional group consists of two amide groups next to each other in reverse mode, connected by two consecutive carbonyl groups, which has been extensively used as supramolecular synthon to generate LMWGs [50][51][52][53][54][55][56][57][58]. A variety of bis, homo and hetero-functionalized bolaform, oxalamide-based gelators have been reported over the past two decades [50][51][52][53][54][55][56], while only two reports of mono-functionalized, primary oxalamide gelators exist to date [57,58].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[291] Their antimicrobial applications [292] can be explored as biomedical coating materials. [293] Myriad gelators scaffolds are available based on phenolic, [294] amide functionality [295] or carboxylate moeity, [296] acylhydrazone, [297] nucleoside: [298] guanosine, [299] sugar, [300] Schiff base, [301] naphthalene diimide, [302] bis(L-Leu-oxalamide), [303] bis(amino alcohol)oxalamide, [304,305] bisphenol A, [306] 1,3 : 2,4-dibenzylidenesorbitol, [307] barbiturate [308] amino acids viz. histidine [309] or alanine-based, [45] peptide/ peptidomimetics, [21,49] steroid, [7] other nitrogen-based [310] benzimadzole, terpyridine, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic work of Žinić et al on the gelation properties of bis­(amino acid) ( I ) and bis­(amino alcohol) oxalamide ( II ) gelators (Figure a) showed that gelation is governed by strong and directional intermolecular hydrogen bonding of the oxalamide units. Moreover, the symmetrical oxalamides that contained achiral amino acids or were meso diastereomers crystallized in contrast to those containing chiral amino acids or amino alcohols, which tended to form gels in certain solvents. , …”
Section: Introductionmentioning
confidence: 99%